Vocal function after transoral videolaryngoscopic surgery (TOVS) for hypopharyngeal and supraglottic cancer. (3rd April 2017) - Tanaka, Shingo; Tomifuji, Masayuki; Araki, Koji; Uno, Kosuke; Tanaka, Yuya; Mizokami, Daisuke; Suzuki, Hiroshi; Miyagawa, Yoshihiro; Taniai, Shinichi; Shiotani, Akihiro
Abstract: Conclusion: The resection of the medial and lateral pyriform sinus was associated with post-operative voice impairment after TOVS. Scar contracture around the cricoarytenoid joint lead to arytenoid fixation toward lateral position, and this wound healing process caused insufficient glottis closure. Although oncological and functional outcomes of TOVS was satisfactory, surgeons should mention the risk of post-operative voice impairment in pre-operative counseling. Objectives: Transoral surgery is a minimally invasive treatment option for hypopharyngeal and supraglottic cancer. Post-operative vocal function was satisfactory in most cases, but in some cases vocal cord was fixed and occasionally voice impairment persists. Methods: Vocal function of 55 patients who underwent transoral videolaryngoscopic surgery (TOVS) for hypopharyngeal and supraglottic cancers was evaluated by the GRBAS perceptive scale, aerodynamic tests and acoustic analyses, and the Voice Handicap Index questionnaire. The risk factors for voice impairment were identified. Results: Voice impairment (G score ≧2) was found in 16 cases (29.1%). Univariate analysis revealed that the resection of medial and lateral pyriform sinus ( p  = .0018) and neck dissection ( p  = .0421) were associated with post-operative voice impairment. Multivariate analysis revealed that the resection of medial and lateral pyriform sinus ( p  = .0021) was associated with post-operative voice impairment.